ANALISIS MORFOSINTAKTIS KONSTRUKSI BERPREFIKS NEGATIF BAHASA INGGRIS - Muhassin, Mohamad (Universitas Islam Negeri Raden Intan Lampung, 2015)
This research entitled “Analisis Morfosintaktis Konstruksi Berprefiks Negatif Bahasa Inggris” has two main objectives, i.e. (i) formulating and analyzing types of derivational construction of English negative prefixes; and (ii) formulating and analyzing the constructions of English negative prefixes based on morphosyntactic analysis. This is a kind of descriptive-qualitative research which employs a distributional method in data analysis with the underlying theories of morphology, syntax. The data are sentences containing the construction of English negative prefixes, taken from English novels and textbooks. The result of the research shows that the class and meaning changing derivation includes (1) deverbal noun: un- + V; (2) deadjectival noun: un- + Adj; (3) denominal verb: dis + N; (4) deadjectival verb: dis- + Adj; (5) denominal adjective: non- + Adj, and class maintaining derivation includes (6) nominal: anti- + N; (7) verbal: un- + V; (8) adjectival: dis- + Adj; and (9) adverbial: im- + Adv. Morphologically, the constructions consist of (a) two constituents, (b) three constituents, and (c) four constituents. Syntactically, the constructions cover head-modifier in NP, VP; head in AdjP; directive and coordinative in exocentric phrase.